An analysis of diatoms as biological indicators of water quality in rivers of the Western Cape - Slingers, Oliver (Department of Environmental and Geographical Science, 2016)
In South Africa the systematic collection of water samples from surface waters and the collation of results is the responsibility of the Department of Water and Sanitation, previously the Department of Water Affairs and Forestry. Local authorities and private contractors are also responsible for conducting water quality tests for reporting purposes. In most cases, samples are collected by hand at predetermined sites and intervals across the country, and are tested for a standard set of parameters that covers various physical, chemical and bacteriological water quality measures. This approach and method of monitoring is time consuming, expensive and requires a high level of skills and capacity to achieve a representative and reliable sample. There is no immediate substitute, although there is a resurgence of interest in the use of bio-indicators in monitoring rivers. In this study, diatoms are investigated as an indicator of water quality because of the relative abundance of species and the ease with which they can be collected in the field, and the establishment of taxonomies of species that are aligned to pollution levels. There is limited knowledge about diatoms species found in lotic conditions, and in seasonal conditions in a Mediterranean climate where the surface water is slightly acidic. This study investigates the use diatoms in lotic waters of the Western Cape and compares this information to surface water quality measurements in the upper and middle course of the Berg River. The study commences by establishing baseline information of diatoms species for the upper to middle section of the Berg River which coincides with sites where surface water samples are regularly collected by the Department of Water and Sanitation. The study was conducted over a 12 month period in order to analysis the response of species to seasonal change and in relation to changing conditions at various point sources of where there is a known discharge into the Berg River. Species and population will be compared to the typological classification of diatom species and in relation to surface water quality. The study seeks to understand how diatoms respond to acidic waters of the Berg River; to measure the response of diatoms to changes in the water quality along the length of the river; and to determine the response of diatom species to point sources discharging water of varying quality into the river.